LEVERAGING ECONOMIC INCENTIVES FOR SUSTAINABLE AGRICULTURE TO ACHIEVE FOOD SECURITY BY 2047 - G. Purushotham (ShodhKosh: Journal of Visual and Performing Arts, 2024)
India stands at a crucial crossroads in its agricultural evolution. With its population projected to reach 1.6 billion by 2047, ensuring food security while embracing sustainability is imperative. Agriculture, employing 42% of the workforce and contributing 17.8% to GDP, faces mounting threats from climate change, soil degradation, and water scarcity. The Green Revolution boosted food production but left a legacy of excessive chemical use, groundwater depletion, and declining soil fertility. To meet the projected food grain demand of 402-437 million tonnes by 2047, India must transition to sustainable agriculture without compromising productivity or farmer livelihoods.